Population Diet and Palaeoenvironment in the 16th–18th c Rusų str. 5 Vilnius: Insights from the Archeobotanical Analysis and Historical Sources - Indrulėnaitė-Šimanauskienė, Vida; Girlevičius, Linas; Motuzaitė Matuzevičiūtė, Giedrė (Archaeologia Lituana, 2022)
The article presents the results of archaeobotanical research from Vilnius, Rusų str. 5. The waterlogged sediment samples were taken from various archaeological contexts dated between the 16th–18th centuries. The abundance of botanical material and large diversity in plant species revealed the diet of past Vilnius inhabitants, the past use of diverse fruit species brown in orchards and in the forest, as well as exotic plants that were likely imported all the way from the southern Europe. The local ruderal vegetation infers of the past local environment at the excavated site.
Keywords: archaeobotanical research; exotic plants; bioarchaeology; Rusų str. 5, Vilnius